2004
DOI: 10.1387/ijdb.041888rf
|View full text |Cite
|
Sign up to set email alerts
|

Evolving eyes

Abstract: Despite the incredible diversity among extant eyes, laws of physics constrain how light can be collected resulting in only eight known optical systems in animal eyes. Surprisingly, all animal eyes share a common molecular strategy using opsin for catching photons, but there are a diverse collection of mechanisms with proteins unrelated to each other used to focus light for vision. However, opsin is expressed in either one of two types of photoreceptor that differ fundamentally in their structure and tissue of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
(44 reference statements)
0
27
0
Order By: Relevance
“…We know that the threshold to elicit a number of withdrawal responses in Lymnaea is reduced when the snail detects a predator (Orr et al, 2007), indicating that these behaviors are modified by the snail's environment. It is also possible that dermal photoreceptors play a role in Lymnaea to entrain its circadian rhythm, as in other species (Berson et al, 2002;Fernald, 2004;Fernald, 2006;Lyons et al, 2006). This issue, as well as the role played by RPeD11 in mediating and/or modulating the animal's circadian rhythm, requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…We know that the threshold to elicit a number of withdrawal responses in Lymnaea is reduced when the snail detects a predator (Orr et al, 2007), indicating that these behaviors are modified by the snail's environment. It is also possible that dermal photoreceptors play a role in Lymnaea to entrain its circadian rhythm, as in other species (Berson et al, 2002;Fernald, 2004;Fernald, 2006;Lyons et al, 2006). This issue, as well as the role played by RPeD11 in mediating and/or modulating the animal's circadian rhythm, requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…One, the developing tooth bud: teeth develop from migration of neural crest cells (Chai et al, 2000;Mitsiadis et al, 2003;Zhang et al, 2003;Hao et al, 2004;Miletich and Sharpe, 2004). Two, the retina of the eye: eyes develop from the neural plate and the optic vesicle is considered as part of the brain (Fernald, 2004;Gehring et al, 2004). Cells of the retinal ganglion cell layer, and possibly bipolar cells of the inner nuclear layer, as well as the rod and con layer, all of neuronal origin, were found to express tuftelin mRNA and protein.…”
Section: Results and Discussion Expression And Localization Of Tuftelmentioning
confidence: 99%
“…Polyphyletic eye evolution is consistent with the facts that the morphology of the photoreceptors (retinal cells containing the protein, opsin, which coverts light to an electrical signal allowing vision) and the phototransduction signaling cascades (the linked biochemical processes in photoreceptors converting light into a nerve impulse) of invertebrates and vertebrates are generally different (except see last section of this review): invertebrates have rhabdomeric (microvillar) photoreceptors and employ a phospholipase C-based phototransduction cascade, while vertebrates have ciliated photoreceptors and employ a phosphodiesterase-based phototransduction cascade (Fernald 2004(Fernald , 2006Land and Nilsson 2002; see Gregory, this issue for further discussion). Moreover, early studies suggested that photoreceptors evolved 40-60 times (Salvini-Plawen and Mayr 1977), although this idea was challenged by Eakin, who believed that all ciliated photoreceptors had a common ancestor (Eakin 1979).…”
Section: Are Eyes Monophyletic or Polyphyletic?mentioning
confidence: 99%
“…Indeed, Land and Nilsson (1992) require that eyes must have the ability to detect an image, no matter how crude, by simultaneously comparing light from different directions; that is, eyes must have spatial vision. Although it is not possible to determine at present, if ever, how many times a light-responsive cell (photoreceptor) combined independently with a darkshielding cell or other structure to create a primitive eye spot, I review here some salient features that favor the idea that diverse eyes have evolved with a considerable degree of independence and have different levels of homology (Land and Nilsson 2002;Fernald 2004).…”
Section: Introductionmentioning
confidence: 99%